2013
DOI: 10.4236/wjcmp.2013.34036
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Dependence of the Density of States in Semiconductors

Abstract: The temperature dependence of the density of energy states in semiconductors is considered. With the help of mathematical modeling of the thermal broadening of the energy levels, the temperature dependence of the band gap of semiconductors is studied. In view of the non-parabolic and the temperature dependence of the effective mass of the density of states in the allowed bands, graphs of temperature dependence of the band gap are obtained. The theoretical results of mathematical modeling are compared with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
0
10
0
3
Order By: Relevance
“…A mathematical model of the density spectrum of states was constructed in [4,5,6]. With the help of which, the temperature dependence of discrete energy levels in the forbidden zone of silicon was analyzed.…”
Section: A Model Of the Temperature Dependence Of The Density Spectrmentioning
confidence: 99%
“…A mathematical model of the density spectrum of states was constructed in [4,5,6]. With the help of which, the temperature dependence of discrete energy levels in the forbidden zone of silicon was analyzed.…”
Section: A Model Of the Temperature Dependence Of The Density Spectrmentioning
confidence: 99%
“…Moreover, the coefficient of expansion is the energy density of states, which does not account for thermal broadening of the levels. At absolute zero, GN-function turns into the Dirac delta function [5]- [7]. When the temperature tends to absolute zero density of states turn to the expansion coefficients in a series of GN-functions.…”
Section: Modelmentioning
confidence: 99%
“…In [5], it was shown that the continuous spectrum defined at room temperature, are formed by the thermal broadening of the number of discrete levels in the band gap. Thermal broadening of the energy states of the conduction band and valence band gap of the semiconductor explains the temperature dependence of the band gap of the semiconductor [6].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations